The Construct of Trust: An Assessment of Measurement Invariance across Three Cultures - Wasti, S. Arzu (Institutional Knowledge at Singapore Management University, 2004)
In recent years, the model of dyadic trust developed by Mayer, Davis and Schoorman (1995) has gained considerable popularity in the U.S. trust literature. In this paper, we evaluate the measurement invariance of the scales developed by Mayer and Davis (1999) across three cultures: U.S., Turkey and Singapore. Our results indicated that of the four proposed antecedents to trust, the propensity to trust scale had unacceptably low reliability across all three cultures and therefore was eliminated from further analyses. Confirmatory factor analyses conducted with each sample separately revealed that while the four factor model in which the other three antecedents of trust, namely, ability, benevolence and integrity and trust itself were allowed to load on their respective factors yielded the best fit for the Singapore and US samples, the unusually high correlation between benevolence and integrity in the Turkish sample resulted in estimation problems. Further analyses conducted with the US and S samples also indicated that the four scales demonstrated metric invariance, suggesting that substantive correlational hypotheses could be tested across these two cultures with the scales developed by Mayer and Davis (1999).